RESPON PENGGUNAAN LIMBAH CAIR AMPASTAHU TERHADAP PERTUMBUHAN DAN PRODUKSI PAKCOI(Brassica rapa) - Kamsia Dorliana Sitanggang (JURNAL AGROPLASMA, 2019)
Today many processed foods using basic materials out. The growing industry out even more rapidly and produce abundant waste. Industrial know in the treatment process generates solid waste and liquid waste. Solid waste is generated from the screening process and clotting, this waste is usually processed into tempe gembus and fodder. The liquid waste is generated out of the washing process, boiling and printing out, therefore the volume of wastewater produced is very high.Waste know will cause a lot of environmental problems. Liquid waste contains high levels of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Total Suspended Solids (TSS), Total Dissolved Solids (TDS) and acidity (pH) is high. However, effluent, rich in organic matter such as proteins, carbohydrates, fats, oils and much more. The study was therefore to utilize liquid waste know as ameliorant land will be required.This research aims to use wastewater know that abundant in society as ameliorant soil to improve plant growth and production. This study uses a randomized complete block design (RBD) with four treatments (0 ml, 100 ml, 250 ml and 400 ml / plant). Plants indicators used in this study is pakcoi mustard (Brassica few).The results showed that the liquid waste out can improve soil chemical properties and a positive influence on the growth and yield of pakcoi. Giving liquid waste out with a dose of 400ml / plant gives the best results in improving soil fertility, growth and crop production pakcoi. Keywords: Liquid waste Tofu Dregs, Growth and Production of Pakcoi (Brassica rapa)